Eksistensi Tradisi Perayaan Maulid Nabi Muhammad SAW Menurut Tarekat Syattariyah di Jl. Denai Gg. Masjid - Sulaiman, Sulaiman; Harahap, H. Indra (TSAQOFAH, 2024)
This research aims to find out how the existence of the celebration of the Prophet Muhammad's birthday in the Syattariyah order, what the response of the surrounding community is. This type of research is a type of qualitative research which is classified as field research which involves interviews with informants, and this research uses an empirical juridical approach. Where researchers went directly into the field to find out about the existence of the celebration of the Prophet's birthday. And as supporting literature in this research we also use books, journals or other things related to the title of this research. As for the findings in this research, the Prophet's birthday had an impact on the lives of the people around him. The results of this research show that the tradition of celebrating the birthday of the Prophet Muhammad was carried out by the congregation of the Syattariyah congregation at the Bakti Mosque, Jl. Denai Gg. The Medan City Mosque is really different from other maulids in general. This creates disharmony between the old people who still firmly maintain this tradition and the young people who are educated and know what is still worth preserving and what should be eliminated.